Yoko learns to read - Wells, Rosemary (Disney-Hyperion Books, 2012)
Despite the doubts of some classmates and her native-born Japanese mother's inability to read English, Yoko finds the key to reading and catches up with the other students in putting new leaves on the classroom's book tree.